Breakdown Characteristics of Unused Transformer Oil and Olive Oil under AC and DC Voltages at Different Temperature Rate - Nadarajah, Haridchana; Mohd Jamail, Nor Akmal; Mohd Jamail, Nor Shahida; Kamarudin, Muhammad Saufi; Baharom, Md Nor Ramdon; Kamarudin, Qamarul Ezani; Sies, Mohamad Farid (International Journal of Integrated Engineering, 2022)
This project aim is to investigate the breakdown characteristics of unused transformer oil and olive oil under AC and DC voltage at different temperature rate. HVAC and HVDC breakdown tests are carried out alongside with the hemisphere electrode arrangements. The high voltage test is done in order to observe the performances of the oil samples to attain the highest breakdown AC and DC voltages. In addition, this project needs to be done to see if olive oil as one of the vegetable oil can be an alternative for the conventional transformer oil. Commonly used transformer oil is made from mineral oil and it is declining day by day as its use increases. So as a precaution studies are done with vegetable oils to replace the mineral oil-based transformer insulation fluid. In this study, each oil sample is tested at different temperature rate and has recorded different value of breakdown voltage from the experiment. The gap distance between electrodes is constant and oil samples are heated at different temperature ranges. More voltage is needed to breakdown at higher temperature rate. Both the unused transformer oil and olive oil have linearly increased AC and DC breakdown voltages when subjected to higher temperatures. However, it is found that the highest AC and DC breakdown voltages are recorded at the highest temperature range and when the insulating medium used is olive oil. Moreover, the obtained AC and DC voltages are then be used to study the electric field in FEMM software